DEVELOPING STUDENTS' READING COMPREHENSION BY USING LITERATURE CIRCLE - Kardi Nurhadi (Universitas Wiralodra, 2017)
The objective of the research is to develop students’extensive reading by using Literature Circle. According to Daniels (2002) literature circle is an activity in which members meet to discuss and respond to a book that they are all reading. The writer used classroom action research as the research method. The steps of action research consist of planning, acting, observing and evaluating. The research participants took from the eleventh grade students of MAN Indramayu. Based on the learning activities from the first to second cycle, it showed there was an improvement of students extensive reading; it can be seen by the students progress of activity from the first to the second cycle, also the students showed a positive respond to the literature circle. From this research finding, it showed that story Literature Circle could develop the students’ extensive reading.